2017
DOI: 10.1684/ecn.2018.0402
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic time dependence of intra-tumoural IFNγ mRNA and protein in patients with breast cancer followed for 14 years after surgery and radiotherapy, without subsequent systemic therapy

Abstract: To cite this article: Todorović-Raković N, Radulovic M, Vujasinović T, Milovanović J, Nikolić-Vukosavljević D. The prognostic time dependence of intra-tumoural IFN␥ mRNA and protein in patients with breast cancer followed for 14 years after surgery and radiotherapy, without subsequent systemic therapy. Eur. Cytokine Netw. 2017; 28(4): 151-6 ABSTRACT. There is increasing evidence for the importance of immunity in breast cancer. IFN␥ is expected to have a prognostic value based on its major role in innate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…Over the entire period of 14 years of follow-up neither IFN-γ mRNA nor IFN-γ protein levels were significantly associated with breast cancer outcome by ROC analysis or Cox regression criteria, but intratumoral IFN-γ mRNA was associated significantly with favorable disease outcome over the first 7 years of follow-up. [19]. The current study demonstrates the prognostic value of measuring IFN-γ in the serum of patients with breast cancer; this allows easy sampling and repeated measurements.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Over the entire period of 14 years of follow-up neither IFN-γ mRNA nor IFN-γ protein levels were significantly associated with breast cancer outcome by ROC analysis or Cox regression criteria, but intratumoral IFN-γ mRNA was associated significantly with favorable disease outcome over the first 7 years of follow-up. [19]. The current study demonstrates the prognostic value of measuring IFN-γ in the serum of patients with breast cancer; this allows easy sampling and repeated measurements.…”
Section: Discussionmentioning
confidence: 61%
“…In our previous study, based upon the long-term follow-up of 73 pN0M0 breast cancer patients after surgery & radiotherapy receiving no subsequent systemic therapy, we investigated the prognostic value of intratumoral IFN-γ mRNA and protein levels [19]. Over the entire period of 14 years of follow-up neither IFN-γ mRNA nor IFN-γ protein levels were significantly associated with breast cancer outcome by ROC analysis or Cox regression criteria, but intratumoral IFN-γ mRNA was associated significantly with favorable disease outcome over the first 7 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…For this review, 45 studies were retrieved from PubMed and another 2 by searching the bibliographies of other papers. Of these, only 15 studies [27,28,29,30,31,32,33,34,35,36,37,38,39,40,41] were included in the analysis, and the reasons for exclusion are reported and detailed in the Supplementary Materials (Table S1). Results of the studies included in our analysis are reported in Table 1 and Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Todorović-Raković et al [30] adopted longer timepoints analyzing the protein and mRNA at the intratumoral level up to 14 years after RT and revealed a consistent prognostic association of IFN-γ protein with a poor disease outcome in patients with a longer follow-up (>7 years). Similarly, for IFN-γ mRNA, a peculiar time-dependent prognostic shift has been reported: from 6 months after RT and until 7 years, IFN-γ mRNA is associated with a good outcome, whereas in patients with a longer follow-up (>7 years), it has been related to a poor prognosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation